PENENTUAN UMUR TAMBANG BANCUH TAK TERPISAHKAN PADA PT SUMBER ANUGRAH BUANA KABUPATEN SORONG - Setyo Age Saputro; Jance Murdjani Supit (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
The mining industry is one of the complex industries, due to its several stage of activities. In the exploration phase one of the activity is interpretation of resources/reserves. In interpreting, one of the method used is the Cross Section method using AutoCAD. This research aims to find out the remaining reserves, comparing the estimated results of mined reserves with the actual results of mined reserves and also the mine remaining life time at the PT Sumber Anugrah Buana 28,532.603m2 mining site. The result of calculation of remaining reserves is 3,015,887.010m3. The actual data of the company's mined reserves amounted to 40,903m3, while the estimated result of the calculation using the cross section method amounted to 277,635.953m3, resulting in a difference of 236,732.953 m3. The remaining life time of the mine is 12 years.